A new genus, with a new species, from Brazil (Acari: Prostigmata: Cunaxidae) - de Castro, Tatiane Marie Martins Gomes; Heyer, Jacob Den (Zootaxa, 2008)
A new cunaxid genus from Brazil, Cunaxatricha gen. nov., is erected and its type species, Cunaxatricha tarsospinosa sp. nov. is described and figured. A key to the genera of the subfamily Cunaxinae, to which this new genus belongs, is provided.